2019
DOI: 10.3389/fpls.2019.00047
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Biostimulant Action of Vegetal-Derived Protein Hydrolysates by High-Throughput Plant Phenotyping and Metabolomics: A Case Study on Tomato

Abstract: Designing and developing new biostimulants is a crucial process which requires an accurate testing of the product effects on the morpho-physiological traits of plants and a deep understanding of the mechanism of action of selected products. Product screening approaches using omics technologies have been found to be more efficient and cost effective in finding new biostimulant substances. A screening protocol based on the use of high-throughput phenotyping platform for screening new vegetal-derived protein hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 64 publications
1
80
0
1
Order By: Relevance
“…The legume-derived PH biostimulant obtained through enzymatic hydrolysis contains 75% of free amino acids and peptides, 22% of carbohydrates and 3% of mineral nutrients. The detailed aminogram of the product along with the phenolics, flavonoids and elemental composition were reported by Rouphael et al [31] and Paul et al [25]. The PE biostimulant obtained by fermentation of tropical plants contains 54% of free amino acids and peptide, 17% carbohydrate, 23% mineral nutrients, 6% vitamins and 0.22% phytohormones as reported in detail by Rouphael et al [33] and Caruso et al [32].…”
Section: Growing Conditions and Experimental Protocolmentioning
confidence: 73%
See 1 more Smart Citation
“…The legume-derived PH biostimulant obtained through enzymatic hydrolysis contains 75% of free amino acids and peptides, 22% of carbohydrates and 3% of mineral nutrients. The detailed aminogram of the product along with the phenolics, flavonoids and elemental composition were reported by Rouphael et al [31] and Paul et al [25]. The PE biostimulant obtained by fermentation of tropical plants contains 54% of free amino acids and peptide, 17% carbohydrate, 23% mineral nutrients, 6% vitamins and 0.22% phytohormones as reported in detail by Rouphael et al [33] and Caruso et al [32].…”
Section: Growing Conditions and Experimental Protocolmentioning
confidence: 73%
“…Tropical plant extract (PE) and especially legume-derived protein hydrolysates (PHs) obtained from vegetal origin proteins have been drawing interest in world agricultural areas, compared to animal-derived ones, due to both their higher agronomic value [16] and no use constraints in organic farming. Moreover, PE or PH application to leaves and/or roots reportedly elicit physiological processes, thus resulting in enhancement of growth [17,18], production and quality [18,19], tolerance to abiotic stressors, such as drought, soil and water salinity, extreme temperature, nutrient deficiency, soil acidity and alkalinity [11,[20][21][22][23][24][25]. Notably, PE or PHs also encourage plant activity of key enzymes involved either in N or C metabolism [12,24,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Paul et al [118] found that tomato plants treated with protein hydrolysates were characterized by a higher content of, e.g., low-molecular-weight phenolic compounds, phytohormones (polyamines), hydroxy-carotenoids, poly-hydroxy fatty acids, and membrane lipids (glycoand phospholipids). They suggest that the metabolic changes caused by treating plants with protein hydrolysates can be correlated with a relatively small number of processes that converge toward the ROS-related (reactive oxygen species-related) plant signaling network.…”
Section: Discussionmentioning
confidence: 99%
“…They suggest that the metabolic changes caused by treating plants with protein hydrolysates can be correlated with a relatively small number of processes that converge toward the ROS-related (reactive oxygen species-related) plant signaling network. Increasing the content of secondary metabolites, such as phenols and carotenoids, which play a key role in protecting plants against oxidative stress [62,102,119], suggests fine-tuning of ROS signaling in plants after the application of protein hydrolysates [118]. In addition, the use of animal protein hydrolysates had a positive effect on the content of protein, phenols, and flavonoids in bananas [120], and vegetal protein hydrolysates stimulated an increase in the content of phenolic compounds and anthocyanins in grape [55].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to underline that the biostimulant activity must not depend on the product's nutrients or natural plant hormones content. The mechanisms activated by biostimulants are often difficult to identify and are still under investigation [58]. High-throughput phenotyping and omic technologies seem to be useful approaches to understand biostimulants activity and hypothesize a mode of action [59][60][61].…”
Section: Biostimulantsmentioning
confidence: 99%